INTEGRATION OF LINGUISTIC LEVELS IN THE PHILOGICAL RESEARCH OF ARTISTIC TEXT: FINAL THEORETICAL CONCLUSIONS AND PROSPECTIVE DIRECTIONS - Yo`ldoshev Dilmurod,Qurbonov Jahongir (International Journal of Literature and Language Studies, 2026)
. This article summarizes the final results of a comprehensive study on the integration, hierarchy and integrity of linguistic levels in the philological study of artistic text and outlines future research prospects. The interrelation of seven linguistic layers, from the phonetic-phonostylistic level to the pragmatic-cognitive level, and their functionality in forming a literary text as a holistic aesthetic system are examined through proven conclusions based on examples of Uzbek classical and modern literature. The role of alliteration, assonance, contextual meaning, synonymy, antonymy, phraseologisms, grammatical forms, sentence types, inversion, trope types and artistic arts in determining the individual author's style, as well as the main conclusions and recommendations on the theory of concepts and the analysis of the linguistic entity are formulated.